Stakeholders of sustainability transition: interventions in energy and Bangladesh RMG industry - Shajahan, Sadril; Nourin, Sabrina; Islam, Md. Faizul; Kaium, Md. Abdullah Al (Routledge, 2024)
This study is grounded in the extent of engagements and exploration of strategies of non-state actors who interact in the intersection between the export intensive Bangladesh Ready Made Garments (RMG) industry, and its energy interventions, such as rooftop solar panels for renewable energy and energy efficiency machines. Given that there lies a limited number of non-state actors within such intersection, in this study we adopt qualitative research design and conduct case analysis on relevant stakeholders such as suppliers, buyers, renewable energy services companies, international organizations, research organizations and financial institutions, following an extent literature on sustainability transition, strategic management, LEED certification, Global Value Chain (GVC) of apparel industry, and stakeholders management. Our findings clearly show the contributions of these actors during an underpinning transition period of Bangladesh RMG industry toward sustainability which can be understood in terms of underlying policies, reputation management and crisis management when it comes to energy interventions. Overall, the study bridges the existing knowledge gap through identification of different level of complex engagements of actors including non-state actors, state actors and new emerging actors through contextualization of different strategies, including proactive and reactive strategies, undertaken by the non-state actors of Bangladesh RMG industry for energy interventions during transitions toward sustainability.